Literature Review on A Nation Competitiveness - Toni Yoyo (Komunitas Dosen Indonesia, 2021)
Competitiveness is a relatively new field of economic knowledge. The concept of competitiveness has developed rapidly since the 1980s. The aim of this study is to review theories on how to assess a nation competitiveness. This study used literature review encompassing articles, journals, and books in relation to competitiveness. The result of this study shows that the scientific approach to measuring and analyzing competitiveness can be conducted through qualitative and quantitative approaches, namely modeling approach, indicator approach, and weighted summation approach. The size of the competitiveness index with a weighting system has been used in global competitiveness report made by the International Institute for Management Development (IMD) and the World Economic Forum (WEF).